Legality of Use of Cryptocurrency as a Marriage Dowry in Indonesia Perspective Compilation of Islamic Law and the Indonesian Ulama Council - Lia Novita Sari; Ishaq; Sri Lumatus Sa'adah (Jurnal Syntax Admiration, 2023)
In recent years, there has been a shift in giving dowries from dowries in the form of money, gold and other goods whose physical form is shifted to digital dowries such as cryptocurrency dowries, a digital currency using blockchain technology. The research focus and objectives of this research are to find out 1) What is the phenomenon of using cryptocurrency as a wedding dowry in Indonesian society. This type of research is normative legal research. The approach in this research uses the Statute Approach and the Case Approach and the Statute Approach. The technique for collecting legal materials is carried out using documentation methods. The results of this research show that the phenomenon of using cryptocurrency as a dowry among Indonesian people, especially Indonesian Muslims, has varied views and not a single perspective.